2017
DOI: 10.1007/s13197-017-2751-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic dehydration with sorbitol combined with hot air convective drying of apple cubes

Abstract: The aim of the present work was to study the effect of the osmotic dehydration (OD) pre-treatment on the mass transfer kinetics and water activity (a) of apple cubes during hot air drying. The adequacy of different mathematical models to describe the moisture content of the product during this process was also evaluated. Apple cubes were osmotically dehydrated with sucrose or sorbitol solutions at 60 °C, and then dried by air at 25-80 °C. Overall, the OD and rise of the air temperature resulted in an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The mass transfer achieved by the removal of water and the solute uptake (glycerol effect) into the peach tissue during OD reduced a w , leading to a stable product suitable for further processing, without compromising its quality. Temperature and glycerol concentration increase also promoted a w decrease …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The mass transfer achieved by the removal of water and the solute uptake (glycerol effect) into the peach tissue during OD reduced a w , leading to a stable product suitable for further processing, without compromising its quality. Temperature and glycerol concentration increase also promoted a w decrease …”
Section: Resultsmentioning
confidence: 95%
“…Temperature and glycerol concentration increase also promoted a w decrease. 39 Colour change plays a key role in the degradation of total quality and sensory acceptance of fresh-cut fruit tissue. Fresh-cut fruits such as peaches are prone to suffer browning as a result of the enzymatic oxidation of polyphenols by polyphenol oxidase (PPO) in the presence of oxygen.…”
Section: Od Effect On Mass Transfer and Qualitymentioning
confidence: 99%
“…OD is usually followed by i.e., conventional drying due to the relatively high moisture content in OD products [ 3 , 4 , 5 ]. The OD process is commonly performed in sucrose and salt solutions [ 6 , 7 ]; however it might also be conducted in sorbitol [ 8 ], corn syrup [ 9 ], and starch syrup [ 10 ]. Taking into account that a relatively high consumption of those substances might have a negative effect on human health, numerous attempts have been made to search for alternatives [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Figure , water activity, a w , of osmotically dehydrated tomato and cucumber slices, ( T : 35, 45, and 55°C and C glycerol = 50, 55, and 60%w/w) is presented. Osmotic dehydration decreased a w with increase in time, temperature, and glycerol concentration ( p < 0.05) (Assis, Morais, & Morais, ). The a w values of tomatoes and cucumbers during osmotic dehydration were not statistically different ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…It could be concluded that, at higher processing temperatures, the rates of water transfer and solids transfer were higher, and the time required food product to reach a standard value was shorter. However, at higher processing temperatures and shorter processing times, WL was more pronounced than SG (Assis, Morais, & Morais, ).…”
Section: Resultsmentioning
confidence: 99%